The Influence of Institutional Ownership, Proportion of Independent Commissioners, Gender of Female Board of Directors, and Company Size on Company Financial Performance - Ninda Ayu Primadani; Sri Wahyuni; Edi Joko Setyadi; Bima Cinintya Pratama (Asian Journal of Management Analytics, 2022)
This study aims to examine the effect of institutional ownership, the proportion of independent commissioners, the gender of female directors, and company size on the company's financial performance. The population of this study is Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The sampling method used was purposive sampling and 147 samples were obtained. Hypothesis testing using multiple linear regression analysis. The results of the study show that institutional ownership variables, the proportion of independent commissioners, the gender of female board of directors has no effect on company financial performance, and company size has a negative effect on company financial performance, because the bigger the company size, the lower the financial performance.